Perspectives from an in-service teacher UDL action research project - Tucker, L. (Cases on Effective Universal Design for Learning Implementation Across Schools, 2024)
Including universal design for learning in graduate programs for in-service teachers is crucial to increasing the application of the framework in practice. This chapter will introduce an action research assignment within an American UDL graduate course and its impact on teacher practice and student learning. Eight case studies across disciplines and levels will be shared. During this process, teachers identified a classroom challenge, developed a UDL intervention, analyzed student data, and shared implications. In-service teacher reflections will be shared on the continued use of a UDL approach beyond their course work and its impact on their teaching practice. The chapter will begin with an introduction to the context of the implementation, investigation questions, methodology, case study presentation, discussion, and conclusion. © 2024, IGI Global.
Keywords: dept.sed